Rice false smut pathogen: implications for mycotoxin contamination, current status, and future perspectives - Zhou, Lei; Mubeen, Mustansar; Iftikhar, Yasir; Zheng, Hongxia; Zhang, Zhenhao; Wen, Junli; Khan, Raja Asad Ali; Sajid, Ashara; Solanki, Manoj Kumar; Sohail, Muhammad Aamir; Kumar, Ajay; Massoud, Ehab El Sayed; et al. (Frontiers in Microbiology, 2024)
Rice serves as a staple food across various continents worldwide. The rice plant faces significant threats from a range of fungal, bacterial, and viral pathogens. Among these, rice false smut disease (RFS) caused by Villosiclava virens is one of the devastating diseases in rice fields. This disease is widespread in major rice-growing regions such as China, Pakistan, Bangladesh, India, and others, leading to significant losses in rice plantations. Various toxins are produced during the infection of this disease in rice plants, impacting the fertilization process as well. This review paper lightens the disease cycle, plant immunity, and infection process during RFS. Mycotoxin production in RFS affects rice plants in multiple ways, although the exact phenomena are still unknown.